Windows 10 Revealed The Universal Windows Operating System for PC, Tablets, and Windows Phone - Jangla, Kinnary. (Apress : Imprint: Apress, 2015)
Windows 10 Revealed is your essential step-by-step guide to using a desktop, laptop, Surface or Windows Phone running Microsoft Windows 10, providing a complete resource for both the beginner and the enthusiast. Techniques are illustrated step-by-step using photography and screen shots throughout, together with concise, easy to follow text from an established expert in the field, providing a comprehensive guide to Windows. Whether you have just bought your first computer, laptop or are a keen computer user who has just upgraded to Windows 10, this book will provide you with a firm grasp of the underpinning foundations and equip you with the skills needed to use a computer like a pro.